2022
DOI: 10.3389/fsurg.2022.1002100
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of clinical effects of microscopic unilateral laminectomy bilateral decompression (ULBD) versus biportal endoscopic ULBD for lumbar canal stenosis

Abstract: OsbjectiveSeveral studies have shown that both microscopic unilateral laminotomy bilateral decompression (ULBD) and unilateral biportal endoscopic (UBE) ULBD are effective for treating lumbar canal stenosis (LCS). However, there are different viewpoints as to which surgical technique is superior. Therefore, this meta-analysis investigated the clinical efficacy and side effects of microscopic ULBD and UBE ULBD for treating LCS.MethodsTo identify relevant studies describing the clinical outcomes and complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…According to a meta-analysis, 27 UBE ULBD complications occurred in 5.8% cases, and the most prevalent complications were dura tear and hematoma. In our study, the total complication rate of UBE surgery was 9.8%, which was higher than the previous report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a meta-analysis, 27 UBE ULBD complications occurred in 5.8% cases, and the most prevalent complications were dura tear and hematoma. In our study, the total complication rate of UBE surgery was 9.8%, which was higher than the previous report.…”
Section: Discussionmentioning
confidence: 99%
“…According to a meta-analysis [27] , the incidence of UBE ULBD complications was 5.8%, and the most prevalent complications were dura tear and hematoma. In our study, the total complication This article is protected by copyright.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…По данным литературы [22,23,[34][35][36], унилатеральная декомпрессия укладывается в адекватные временные рамки, приводит к небольшой кровопотере и меньшему потреблению анальгетиков в сравнении с классической методикой ламинэктомии. Малоинвазивные методы хирургического лечения приводят к снижению частоты интраоперационных осложнений [37]. Все эти преимущества позволяют проводить подобные вмешательства под местной анестезией при наличии противопоказаний к общей анестезии у коморбидных пациентов [38].…”
Section: Discussionunclassified
“…Heo, [20] in a study with 3 groups (biportal endoscopy, uniportal endoscopy, and microsurgery) with at least 1 year of follow-up, has reported that UBE showed benefits in terms of avoiding postoperative facet joint violation and reduced immediate postoperative pain. Other studies [21][22][23][24][25] have also drawn attention to the advantages of a shorter hospitalization period and less postoperative back pain when compared with microscopic decompression. In our case, the epidural fat stuck with the dura mater was carefully removed with pituitary forceps, and full decompression was confirmed when the medial walls of bilateral pedicles were visualized.…”
Section: Discussionmentioning
confidence: 99%